STUDI TINGKAT PENYALAHGUNAAN NARKOTIKA DAN PSIKOTROPIKA PADA PELAJAR SLTA (SMA/SMK) DI KOTA DENPASAR - Dewi, L.P.Mirah Kusuma; Lestari, A.A.Diah Widya; Wirasuta, I Made Agus Gelgel (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 4 (2014): Indonesian Journal of Legal and Forensic Sciences, 2014)
The level of drug knowledge and drug abuse among senior high school students in Denpasar City has been assessed between January to Mei 2010. A simple random sampling method was used to select the students. Under 90% confidence level was obtained 273 students, who involved in this study. The students were asked to answer the questionnaire to find out their knowledge of drug abuse effects. They also followed a urine screen test using rapid EMIT-test for the amphetamine, methamphetamine, opiate, cocaine, cannabis, and benzodiazepine. More than 95% of students had a not qualified level knowledge of drug abuse effects. We found out a positive correlation between the interest of the students to access drug information online or mass media to their knowledge. Based on screen test result of urine sample has shown that the abuse level on senior high school’s students in Denpasar City was estimated 0.73% benzodiazepine class abuse.
Keywords: drugs, knowledge, drug abuse, student, Denpasar